MJELLT 2020
DOI: 10.47340/mjellt.v1i1.1.2020
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Yemeni University Students’ Attitudes towards Learning Linguistic Courses Using Google Classroom

Abstract: This research paper intends to investigate the attitudes of Yemeni university students towards using Google Classroom as a learning tool. It also aims to explore any similarities and differences between graduate and undergraduate students and between males and females in terms of their attitudes towards using Google Classroom as a learning tool. This study employed a quantitative approach. One hundred and twenty students of the fourth level of the B.Ed. program and forty students enrolled in the M.Ed. program … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…One of the main advantages of Google Classroom is that it is free [24]. It has also been shown that Google Classroom can influence students to become independent learners who study on their own [4]; [25]. Heggart and Yoo (2018) [26] found that students strongly agreed to the use of Google Classroom in teaching and learning because they can access the information from the very same source through a variety of devices such as laptops, mobile phones or tablets any time.…”
Section: Google Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main advantages of Google Classroom is that it is free [24]. It has also been shown that Google Classroom can influence students to become independent learners who study on their own [4]; [25]. Heggart and Yoo (2018) [26] found that students strongly agreed to the use of Google Classroom in teaching and learning because they can access the information from the very same source through a variety of devices such as laptops, mobile phones or tablets any time.…”
Section: Google Classroommentioning
confidence: 99%
“…One of the pertinent models commonly used for this purpose is technology acceptance model [16]. Most studies by researchers in the field have shown that users of Google Classroom view its ease of use, usefulness, and helpfulness in a positive way [4]; [17]- [21]. However, studies on Google Classroom involving Malaysian learners are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…ICT's integration into educational system has led to positive effects [3]. Classrooms with technology-assisted instructions can make learning and teaching not only more effective but also enjoyable [4]. These classrooms make students more motivated to learn about the subjects [4].…”
Section: Introductionmentioning
confidence: 99%
“…Classrooms with technology-assisted instructions can make learning and teaching not only more effective but also enjoyable [4]. These classrooms make students more motivated to learn about the subjects [4]. In higher education institutions, classrooms of this nature can contribute towards improved educational quality [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation